Feeding/Swallowing Disorders: Maintaining Quality of Life in Persons with Intellectual Disability - F. Riquelme, Luis; D. Benjamin, Rebecca; J. Tahhan, Hannah; K. Sandoval, Gracelynn; Alomari, Naga; Soyfer, Alexandra (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Persons with intellectual disability (ID) have received little attention in systematic studies of healthcare and quality of life. Less attention has been provided to specific disorders, such as those impacting the swallowing mechanism. In comparison to the general population, persons with ID experience noticeably greater healthcare inequalities and despite greater life expectancy, it is still lower than the general population. This paper serves as an introduction to healthcare colleagues regarding the risks involved in choking and swallowing disorders in persons with ID, how to evaluate these potential risks and possible treatments. Associated etiologies are presented. A discussion on feeding disorders versus swallowing disorders is also introduced. The inadequacy of swallowing assessment services to persons with ID may be related to the lack of professionals with specialized training in working with this population, reduced funding for research to explore options for improved nutrition and reduced risk of choking and minimal research on changes in feeding skills and/or swallow physiology in this select group of individuals